Strengthening the Link between Economic Growth and Poverty Reduction in Mali : A Poverty Assessment - World Bank (World Bank, Washington, DC, 2021)
This poverty assessment aims to strengthen the analytical foundation for poverty-reduction policies and interventions in Mali. In recent years, important gains have been made across multiple dimensions of household welfare, but poverty in Mali remains widespread and extreme. The COVID-19 induced crisis has reversed much of the progress in poverty reduction achieved in Mali over the last decade. Rural poverty in Mali is strongly associated with employment in low-productivity agricultural activities, large family sizes, and high dependency ratios. Income inequality has increased in recent years, and geographical disparities in wellbeing have widened.